2023
DOI: 10.3390/d15121215
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Expectations: Recent Discovery of New Cave-Restricted Species Elevates the Água Clara Cave System to the Richest Hotspot of Subterranean Biodiversity in the Neotropics

Rodrigo Lopes Ferreira,
Marconi Souza-Silva

Abstract: The Água Clara Cave System was previously recognized as a prominent hotspot of subterranean biodiversity in South America, harboring 31 cave-restricted species. However, a recent expedition conducted in September 2023, coinciding with an exceptionally dry period in the region, provided access to previously unexplored areas. Therefore, the objective of this research was to investigate the cave-restricted invertebrate species, extending the findings from a previous article on the Agua Clara Cave System published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Lukić et al [36] reported that almost all information for the fauna of the Lukina Jama-Trojama Cave System in Croatia dates from the 1990s or later. The same is true for Fern Cave in Alabama [44], Hon Chong in Vietnam [46], and the Água Clara Cave System in Brazil [27,28]. Sampling effort is therefore a major determinant of the richness of species in these caves.…”
Section: Taxonomic Completenessmentioning
confidence: 88%
“…Lukić et al [36] reported that almost all information for the fauna of the Lukina Jama-Trojama Cave System in Croatia dates from the 1990s or later. The same is true for Fern Cave in Alabama [44], Hon Chong in Vietnam [46], and the Água Clara Cave System in Brazil [27,28]. Sampling effort is therefore a major determinant of the richness of species in these caves.…”
Section: Taxonomic Completenessmentioning
confidence: 88%